Effect of calcination temperature on the synthesis of TiO2 nanoparticles from Sutherlandia frutescence for the degradation of Congo red dye and antibiotics ciproflaxin and sulfamethoxazole - Carol Langa; Zikhona N Tetana; Nomso C Hintsho-Mbita (Chemical Physics Impact, 2023)
Considering that pollutants such as dyes and pharmaceuticals are mutagenic and carcinogenic, they provide a major risk to aquatic life and humans, thereby making their removal to be crucial. The current study is focused on synthesizing TiO2 nanoparticles through the utilization of an aqueous extract from Sutherlandia frutescens. FTIR, XRD, SEM, UV–Vis and EDS techniques were employed for the analysis of the attributes of TiO2 nanoparticles. In accordance with FT-IR analysis, The S frutescens plant's unique functional groups were found to be deposited on the TiO2 nanoparticles which were synthesized. At wavelengths of 352 nm and 370 nm, substantial absorption peaks were seen in UV–Vis confirming the TiO2 formation and the bandgaps were calculated and found to be 3,19 eV, 3.26 eV and 3.29 eV for 400 °C, 450 °C and 500 °C respectively. XRD further confirmed, with the anatase peak of the TiO2 synthesis with a 10.17 average crystallite size. SEM showed the materials were spherical in shape, irregular and unevenly distributed on the surface. The synthesized nanoparticles were subjected to assessment for their photocatalytic performance while exposed to the dye Congo red (CR) and the antibiotics sulfamethoxazole (SMX) and ciprofloxacin (CIP). The highest degradation was reported for the TiO2 NPs @ 400 °C at the optimum dosage of 30 mg to be 87 % against 5 ppm CR dye after 120 mins. Upon reusing this material, its efficiency was reduced to 64 % after the first cycle followed by 61 % then 36 % for the second and third cycle respectively. Moreover, Electrons were the entities accountable for the deterioration of the dyes. Testing against the 10 ppm antibiotics, SMX and CIP had degradations of 82 and 94.6 %, respectively, after an exposure of UV (300 W) light for a period of 120 min. This investigation shows that these environmentally friendly materials can be utilized to degrade a variety of contaminants.